Investigating the effects of gender and scaffolding in developing preschool children’s computational thinking during problem-solving with Bee-Bots - Angeli, Charoula; Georgiou, Kyriakoula (Frontiers in Education, 2023)
The research community has embraced computational thinking as an essential skill to develop in school and academic settings. Many researchers argue that computational thinking should be developed in the context of programming and robotic activities in all educational levels of education, starting from early childhood education. However, the factors related to developing computational thinking in preschool education are still under study. Furthermore, not too many empirical investigations provide evidence about the development of computational thinking in young children. The present study examined the effects of scaffolding and gender in developing young children’s sequencing and decomposition skills - two of the five skills that constitute computational thinking. The results indicated statistically significant effects about the type of scaffolding on children’s computational thinking in favor of the children assigned to the experimental groups. Lastly, boys outperformed girls on all occasions, indicating that gender effects exist. The authors conclude that researchers need to design teaching interventions in such a way so they have mathemagenic outcomes for all learners irrespective of gender. Finally, the authors conclude with implications and future research directions.